Основні етапи життєвого циклу формування cтудентських спільнот ВНЗ - Пелещишин, Андрій; Трач, Ольга (Видавництво Львівської політехніки, 2015)
Проаналізовано наявні життєві цикли, суміжні до життєвих циклів віртуальних спільнот та розглянуто їхні особливості. На основі результатів аналізу виділено етапи та напрями життєвого циклу віртуальних спільнот. Описано етапи на прикладі студентських спільнот ВНЗ. The article analyzes the existing life cycles related to the life cycles of virtual communities and examined their characteristics. Based on analysis selected stages and areas of the life cycle of virtual communities. The stages carried out by the example of the students community of universities.
The main stages of the life cycle of the formation of student communities of universities
Keywords: віртуальна спільнота; Інтернет; життєвий цикл; virtual communities; Internet; life cycle